Model Penguatan Jiwa Wirausaha Ramah Lingkungan Berbasis Bank Sampah Sekolah di MI Salafiyah Simbang Kulon 02 - Zulfa, Lailatul; Muhlisin Muhlisin; Bambang Sri Hartono; Roikhatul Jannah (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the gap between the theory and practice of entrepreneurship education in Islamic elementary schools, which is generally still theoretical and not yet integrated with environmental issues. In fact, the green edupreneurship approach emphasizes the importance of fostering an entrepreneurial spirit oriented towards social and ecological sustainability. This study aims to describe the implementation of the School Waste Bank program at MI Salafiyah Simbang Kulon 02 and analyze how these activities shape an environmentally friendly entrepreneurial spirit in students. The research method used is descriptive qualitative with triangulation techniques through observation, in-depth interviews, and documentation involving the principal, teachers, waste bank managers, and students in grades I–VI. Data analysis uses the Miles & Huberman interactive model which includes data reduction, presentation, and drawing conclusions. The results show that the School Waste Bank program is effective in fostering ecological awareness, responsibility, discipline, creativity, and independence in students through activities such as sorting and managing waste as an economic resource. These activities also strengthen project-based learning and contextual social collaboration, thereby forming green entrepreneurial character in students from an early age. Thus, this program becomes a sustainable learning model that integrates entrepreneurial values and environmental awareness.